(untitled) - Streeter, Victor L. (Boston, 1998)
In the revision of this very successful text, many changes have been made in scope, organization, and required prerequisite skills. The authors have increased the scope of the book to include heat and mass transport. BASIC programs have been removed and complex problem solutions are now presented in Microsoft Excel. There is also a new website that will contain substantial information on computing, principal files, and tutorials on the use of MatLab and Mathematica.
Động lực học sông, biển
Keywords: Fluid mechanics; Thủy động lực học